Islamic Educational Values within the Curriculum of Love: A Semantic Analysis of Nasaruddin Umar’s Educational Thought - Nurfadillah Nurfadillah; Abdul Jabbar Tahir; Baso Pallawagau (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the values of Islamic education in the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) proposed by Nasaruddin Umar through a semantic review. The research seeks to explore the deep meanings of key terms in this concept and its relevance as a new paradigm for a more humanistic and transformative Islamic education in Indonesia. This study employs a qualitative approach using library research. Primary data were obtained from Nasaruddin Umar’s original works and official documents from the Ministry of Religious Affairs, while secondary data were drawn from relevant Islamic education literature. Data were analyzed using semantic analysis to examine the meanings of key terms such as cinta (love), rahmah (mercy), and Panca Cinta (Five Loves). The findings reveal that the Love-Based Curriculum is built upon an integrated theological-logos-ethos framework. Through semantic analysis, the terms mahabbah, rahmah, and Panca Cinta (love for Allah and His Messenger, love for self and others, love for knowledge, love for the environment, and love for the homeland) contain holistic meanings that integrate theological, spiritual, humanistic, ecological, and national dimensions. This concept shifts Islamic education from a formalistic approach to one centered on compassion and mercy (rahmatan lil ‘alamin). Theoretically, this study enriches the discourse of Islamic education thought with a semantic perspective. Practically, the Love-Based Curriculum has the potential to serve as a more humanistic and inclusive curriculum model. However, this research is limited to a literature study; therefore, further empirical research is needed to measure the effectiveness of its implementation in educational settings.